The Relationship Between Osteoporosis and Intestinal Microbes in the Henan Province of China - Qin, Qian; Yan, Su; Yang, Yang; Chen, Jingfeng; Yan, Hang; Li, Tiantian; Gao, Xinxin; Wang, Youxiang; Li, Ang; Wang, Shoujun; Ding, Suying (Frontiers in Cell and Developmental Biology, 2021)
We explored the association between gut microbiota composition and osteoporosis (OP) in Chinese by high-throughput metagenome-wide gene sequencing. Compared with controls, several species with altered abundance and specific functional pathways were found in OP group. At the species level, the abundance of Actinomyces graevenitzii, Actinomyce sodontolyticus, Olsenella unclassified, Pantoea unclassified, Streptococcus gordonii, Streptococcus mitis oralis pneumoniae, Streptococcus parasanguinis, Streptococcus sanguinis and Escherichia coli were increased in OP individuals, which were positively correlated to inflammation indicators (WBC, NEC and NLR) and the pathways which were responsible for lactate acid and ethanol fermentation, phytate degradation and LPS biosynthesis. In addition, Streptococcus mitis oralis pneumoniae and Streptococcus sanguinis enrich in OP group were negatively correlated to BMD (P<0.05). On the contrary, the levels of Akkermansia muciniphila, Bacteroides eggerthii, Bacteroides fragilis, Bacteroides uniformis and Butyricimonas synergistic were decreased in OP group which had a negatively correlation with inflammation indicators (WBC, NEC and NLR) and the above pathways (P<0.05). Functional prediction revealed that 106 metabolic pathways enrich in OP group significantly higher than the control group (P<0.05). Especially, especially pathways related to LPS biosynthesis, phytate degradation, lactate acid and ethanol fermentation, were more abundant in OP group than control and were positively related to NEC. Conclusions several species with altered abundance and specific functional pathways were discovered in OP individuals. Our findings provide novel epidemiologic evidence to elucidate the underlying microbiota-relevant mechanism in bone mineral and to promote bone resorption and release of phosphate by adding phytases.